Natural soil and lithium carbonate as economical solid-base catalysts for biodiesel production. (November 2020) - Dai, Yong-Ming; Lin, Jia-Hao; Huang, Shiuh-Tsuen; Lee, Wen-Lian William; Hsieh, Chen-Hsuan; Chen, Fu-Hsuan; Chen, Chiing-Chang
Abstract: Natural soil contains Si and Al compounds suitable for catalysis biodiesel production reactions. Catalytic activity related to biodiesel production was investigated using two soil types mixed with Li2 CO3 as the alkali metal catalysts. The method used for heterogeneous transesterification catalyst preparation using soil was straightforward: one-pot blending and grinding of soil with Li2 CO3 followed by heating at 700 °C for 4 h. The physical and chemical properties of prepared solid-base catalyst were characterized through X-ray diffraction (XRD), Brunauer–Emmett–Teller surface area (BET), Fourier transform infrared spectroscopic (FTIR) and field emission scanning electron microscope (FE-SEM). The optimal conditions for transesterification involved mixing methanol and oil at a molar ratio of 36:1 at 65 °C with 8 wt% alkali catalyst. The results demonstrated that the conversion rate of seven oils to fatty acid methyl esters was in the range of 98%–99%. Thus, the application of natural soil in catalyst preparation for biodiesel production is cost-effective and ecofriendly. Graphical abstract: Highlights: The alkali metal catalysts, TAL2.5-700-4 and LKL2.5-700-4 were prepared from natural soil. The alkali metal catalyst is also successfully tested in the transesterification reaction. Conversion efficiency of soybean oils to biodiesel using alkali metal catalyst can reach 99%.